Tomas C. Vera- Sergio Ramírez de Arellano - Astol, Eugenio (My University, 2018)
El artículo de Puerto Rico Ilustrado brinda datos biográficos de Tomas C. Vera y Sergio Ramirez de Arellano.
Keywords: Vera, Tomas C., 1860-1909; Ramírez de Arellano, Sergio, 1873-1933